2022
DOI: 10.1002/pssb.202100521
|View full text |Cite
|
Sign up to set email alerts
|

Specifics of Spectroscopic Features of Yb3+‐Doped Lu2O3 Laser Transparent Ceramics

Abstract: Some specifics of spectroscopic and laser properties of Yb3+ dopant are shown in Yb3+‐doped Lu2O3 cubic sesquioxide transparent ceramics, a very important laser material, fabricated by Akio Ikesue using the method based on solid‐state mixing of oxides and sintering by hot isostatic pressing (HIP) technique. For instance, despite the simplicity of Yb3+ electronic configuration, it is emphasized that a lot of precautions need to be considered during the evaluation and the assignment of Yb3+ experimental data in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…[1][2][3] It has been demonstrated that Lu 2 O 3 can be doped with various rare-earth (RE) ions for laser emission at different wavelengths, such as Yb 3+ and Nd 3+ at 1 μm, Tm 3+ and Ho 3+ at 2 μm as well as Er 3+ at 3 or 1.5 μm. [4][5][6][7][8][9][10][11][12] Among these trivalent RE ions, doping with Yb 3+ has the least impact on the crystallographic and physical properties of the host due to the comparable mass and ionic radius of metal ions, which results in weak lattice distortions, low scattering losses, excellent thermal properties, and ease to obtain different doping levels. 9,13 It is known that high thermal conductivity at high doping concentrations is advantageous to laser power scaling due to efficient heat dissipation from the gain media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] It has been demonstrated that Lu 2 O 3 can be doped with various rare-earth (RE) ions for laser emission at different wavelengths, such as Yb 3+ and Nd 3+ at 1 μm, Tm 3+ and Ho 3+ at 2 μm as well as Er 3+ at 3 or 1.5 μm. [4][5][6][7][8][9][10][11][12] Among these trivalent RE ions, doping with Yb 3+ has the least impact on the crystallographic and physical properties of the host due to the comparable mass and ionic radius of metal ions, which results in weak lattice distortions, low scattering losses, excellent thermal properties, and ease to obtain different doping levels. 9,13 It is known that high thermal conductivity at high doping concentrations is advantageous to laser power scaling due to efficient heat dissipation from the gain media.…”
Section: Introductionmentioning
confidence: 99%
“…Cubic sesquioxide Lutetia (Lu 2 O 3 ) material has attracted considerable interest as a laser host due to its potential applications in high‐power solid‐state lasers (SSL) 1–3 . It has been demonstrated that Lu 2 O 3 can be doped with various rare‐earth (RE) ions for laser emission at different wavelengths, such as Yb 3+ and Nd 3+ at 1 μm, Tm 3+ and Ho 3+ at 2 μm as well as Er 3+ at 3 or 1.5 μm 4–12 . Among these trivalent RE ions, doping with Yb 3+ has the least impact on the crystallographic and physical properties of the host due to the comparable mass and ionic radius of metal ions, which results in weak lattice distortions, low scattering losses, excellent thermal properties, and ease to obtain different doping levels 9,13 .…”
Section: Introductionmentioning
confidence: 99%